PECULIARITIES OF PROGRAMMATIC AND METHODICAL COMPLEX “TERRA MATHEMATICA” (Journal of Information Technologies in Education (ITE), 2010)
The problems of creation, dissemination, implementation and maintenance of program-methodical complex TerraMathematica. The architecture, methodology content, product features are showed. The structure, architecture, functionality and tasks of the site software support, particularly for its implementation are considered. The value of the product to support extracurricular student learning mathematics, the characteristic features of self-organization of students with educational materials and modules of the complex are investigated. The benefits for parents of students of usage the software are showed.
Keywords: distance learning; math editor; mathematical software; pedagogical software; solver